2017
DOI: 10.1139/gen-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of porcine peripheral blood reveals differentially expressed genes from the cytokine–cytokine receptor interaction pathway related to health status

Abstract: While some research has looked into the host genetic response in pigs challenged with specific viruses or bacteria, few studies have explored the expression changes of transcripts in the peripheral blood of sick pigs that may be infected with multiple pathogens on farms. In this study, the architecture of the peripheral blood transcriptome of 64 Duroc sired commercial pigs, including 18 healthy animals at entry to a growing facility (set as a control) and 23 pairs of samples from healthy and sick pen mates, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…In databases regarding gene expression in tissues, the PB is scarcely considered, and no evidence was found for PYY . The inspection of databases of trials reporting the porcine PB transcriptome supports the Authors’ observation 31 , 43 . It is difficult to explain that the increased expression obtained at weaning in the PB; this could indicate that PYY originates from the presence of reticulocytes or from young erythrocytes.…”
Section: Discussionsupporting
confidence: 77%
“…In databases regarding gene expression in tissues, the PB is scarcely considered, and no evidence was found for PYY . The inspection of databases of trials reporting the porcine PB transcriptome supports the Authors’ observation 31 , 43 . It is difficult to explain that the increased expression obtained at weaning in the PB; this could indicate that PYY originates from the presence of reticulocytes or from young erythrocytes.…”
Section: Discussionsupporting
confidence: 77%
“…Approaches to investigate the host response to S. suis in vivo have been performed in several organisms, including pigs (Li et al, 2010;Liu et al, 2011a;Gaur et al, 2014;Ye et al, 2017), but also non-porcine species, such as zebrafish and mice (Wu et al, 2010;Rong et al, 2012). Confirming the results of in vitro challenged host cells, during these studies genes involved in inflammatory and immune defense responses were identified as DEGs (Li et al, 2010;Liu et al, 2011a;Rong et al, 2012;Ye et al, 2017). Tissues and organs investigated during the porcine in vivo studies covered spleen, brain, lung, monocytes, and peritoneal blood, but not specifically the CP.…”
Section: Introductionmentioning
confidence: 99%
“…Their dynamics re ects homeostatic regulation [1][2][3], physiological changes [4,5] and variations in immune capacity [6,7]. Circulating molecules also provide valuable insights into complex phenotypes such as obesity and diabetes [8,9], health status [10], sensitivity to heat stress [11] and nutrient e ciency for productive outputs [3,7,12]. Therefore, they hold much promise in the identi cation of biomarkers for the prediction of particular phenotypes [13].…”
Section: Introductionmentioning
confidence: 99%